Pengaruh Teknik Storytelling Terhadap Peningkatan Self Confidence Siswa Kelas VII-A di SMP Negeri 1 Hiliduho - Endi Septikad Hulu; Elizama Zebua (Indo-MathEdu Intellectuals Journal, 2023)
Someone who has a high self-confidence attitude will easily make decisions and be more assertive in attitude. But on the contrary, if the person who has a low self-confidence attitude, then the person always feels anxious and hesitant if he decides something. The purpose of this study was to determine the effect of storytelling techniques on the self-confidence of grade VII-A students at SMP Negeri 1 Hiliduho. The research design used was a quasy experiment. The research sample was Class VII-A students as the Experimental Class with a total of 24 people and Class VII-C as the Control Class with a total of 26 students. The results of the study: (1) The percentage level of student confidence using storytelling techniques in the Experimental Class was 87.64% with good criteria and the percentage level of student confidence in the Control Class was 53.69% with Less criteria, (2) Based on the results of the hypothesis test on student confidence, Zcalculate value = 1.892 and Ztabel value = 1.645. Because the value of Zcalculate > the value of Ztabel is 1.892 > 1.645, then reject Ho and accept Ha. So that the hypothesis test which reads: "there is an influence of storytelling techniques on the self-confidence of grade VII-A students at SMP Negeri 1 Hiliduho" was accepted at a significant level of 5%